Preparation and characterization of multifunctional free-standing Ni/epoxy composite films - S. Y. Fu; X. J. Shen; Y. Liu; Q. P. Feng; H. M. Xiao; K. Friedrich (eXPRESS Polymer Letters)
A new method is reported on preparation of multifunctional free-standing Ni/epoxy composite films with comprehensive physical properties under an applied magnetic field. A water soluble poly(vinyl alcohol) film is used as an interlayer film to separate epoxy resin and glass wafer. Ultrafine Ni particles are incorporated into a self-designed flexible-type transparent epoxy resin to get composite films. For the purpose of comparison, random Ni/epoxy composite films are also prepared in the absence of the applied magnetic field. The aligned composite films are endowed with promising optical, mechanical, electrical, and ferromagnetic properties. The specific resistance is 4–9 orders lower in the vertical direction than that in the horizontal plane and the squareness ratio in the vertical direction is about 50% higher than in the horizontal plane. Meanwhile, their transmittance is much higher than that of the random composites. The anisotropies in their electrical and ferromagnetic properties are very useful material characteristics that may be explored for many applications.